2013
DOI: 10.3329/bjb.v42i1.15908
|View full text |Cite
|
Sign up to set email alerts
|

Pollen morphology of the genus Oxytropis DC. in Turkey

Abstract: Pollen morphology of 11 species of the genus Oxytropis DC. (Fabaceae) distributed in Turkey were examined with light (LM) and scanning electron microscope (SEM). Morphology of pollen grains shows isopolar, radially symmetric, tricolporate, prolate or subprolate, porus shape oblate or operculate and exine subtectate. The size varies with the polar axis from 19.52 -33.31 µm and the equatorial axis from 13.50 -25.82 µm. There are five ornamentation types: perforate at equatorial section and psilate at polar secti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 12 publications
2
17
0
Order By: Relevance
“…Pollen morphology has played an important role in legume systematics (Erdtman, 1969;Bronckers et al, 1972;Ferguson and Skvarla, 1981;Kahraman et al, 2013;Ceter et al, 2013aCeter et al, , 2013bPinar et al, 2014). In previous studies, several authors observed the significant variation in pollen sculpture among species of the genus Vigna (Verdcourt, 1970;Bronckers et al, 1972;Stainier, 1974;Maréchal et al, 1978;Wael, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Pollen morphology has played an important role in legume systematics (Erdtman, 1969;Bronckers et al, 1972;Ferguson and Skvarla, 1981;Kahraman et al, 2013;Ceter et al, 2013aCeter et al, , 2013bPinar et al, 2014). In previous studies, several authors observed the significant variation in pollen sculpture among species of the genus Vigna (Verdcourt, 1970;Bronckers et al, 1972;Stainier, 1974;Maréchal et al, 1978;Wael, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Karaman et al (2009) Oxytropis savellanica and O. fominii showed higher genetic variation when only the trnL intron region was analyzed (Figure 1). Ceter et al (2013) indicated that the shortest porus length (2.82 µm) was seen in O. savellanica, whereas the longest (5.04 µm) one was in O. lazica within the native species studied. Hence, the distant location of these two species in the trnL intron tree may be meaningful.…”
Section: Discussionmentioning
confidence: 99%
“…Relationships among species of the genus have been studied based on anatomical and morphological characters such as pollen morphology, seed morphology, stomata, trichome, leaf surface morphology, fruit, and flower structures by several researchers (Dickoré and Kriechbaum, 2006;Kholina and Kholin, 2008;Karaman et al, 2009;Ceter et al, 2013;Erkul et al, 2014). Even though there are numerous studies indicating morphological variations in Oxytropis species, the number of studies in the literature concentrating on phylogenetic relationships among them is limited (Jorgensen et al, 2003;Gao et al, 2009;Archambault and Stromvik, 2012;Artyukova and Kozyrenko, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The family Leguminosae (Fabaceae) is the third-largest family of angiosperms (flowering plants) after the Orchidaceae and the Asteraceae or Compositae, with 727 genera and 19,325 species [1,2], comprising annual and perennial herbs, shrubs, and trees [3]. This family distributed in cold mountainous regions in Europe, Asia, and North America, also has very economic importance [4] which is the main sources of gums, dyes, fuel, timber, medicinals, and pulses [5].…”
Section: Introductionmentioning
confidence: 99%